RELATIONSHIP BETWEEN SUSTAINABLE OUTER SPACE LAW AND THE USE OF SATELLITE TECHNOLOGY IN HANDLING MARINE PLASTIC DEBRIS - Pramudianto, Andreas (Journal of Environmental Science and Sustainable Development, 2019)
Since the discovery of plastic material, which ends up as plastic waste after use and partly enters the sea, it has become a global problem that needs serious treatment. No international agreement exists about handling marine plastic debris. By contrast, national laws have been created to plastic bags and plastic debris. Currently, the existing legal instruments, especially in outer space law, are still traditional and inadequate. A sustainable new paradigm in outer space law is needed, such as the use of satellite technology, such as the COSMOS satellite by RKA Recosmos, for global environmental issues, including the ozone layer, climate change, biodiversity handling of hazardous and toxic waste, and rubbish, including marine plastic. Satellite technology is needed, especially in providing data and information and in observing the movement of plastic waste in the sea. International cooperation is needed to ensure complete and accurate data and information about the spread of marine plastic debris. This study aims to identify and analyze the role of sustainable outer space law in the handling of marine plastic debris using outer space technology such as satellites. The main research is study relations between law of the sea and outer space law. The methodology of this research uses normative legal research. The analysis of this research uses normative and juridical analysis methods. This research show that satellite technology is seldom to use in the study’s marine debris moreover in the international law perspective. Preliminary results show that a sustainable outer space law requires all parties to cooperate and handle marine pollution.